Epifania Chrystusa i królowanie Boga motywacją zachęty w 1Tm 6,11-16 - Haręzga, Stanisław (The Biblical Annals, 2015)
The author of the article presents at first a literary specificity of the text 1 Tm 6:11-16. Next within the exegesis he explains the encouragement towards the trully Christian life (v. 11-12) and the role that performs in it the motive of Christ’s epiphany (v. 15-16) along with the solemn doxology in the honour of God (v. 15-16). The appeal to the truth about God who is the only Ruler, King and God, as well as to the epiphany of Christ should encourage the addressee of the letter 1 Tm to build persistently in the name of Christ the Kingdom of God which He in His ultimate revelation will deliver for ever to God the Father.